Innovative strategies to improve hematopoietic stem cell transplant outcomes in myelofibrosis. Issue 11 (19th July 2022) - Perram, Jacinta; Ross, David M.; McLornan, Donal; Gowin, Krisstina; Kröger, Nicolas; Gupta, Vikas; Lewis, Clinton; Gagelmann, Nico; Hamad, Nada
Abstract: Myelofibrosis (MF) is a clonal myeloproliferative neoplasm characterized by inflammation, marrow fibrosis, and an inherent risk of blastic transformation. Hematopoietic allogeneic stem cell transplant is the only potentially curative therapy for this disease, however, survival gains observed for other transplant indications over the past two decades have not been realized for MF. The role of transplantation may also evolve with the use of novel targeted agents. The chronic inflammatory state associated with MF necessitates pretransplantation assessment of end‐organ function. Applying the transplant methodology employed for other myeloid disorders to patients with MF fails to acknowledge differences in the underlying disease pathophysiology. Limited understanding of the causes of poor transplant outcomes in this cohort has prevented refinement of transplant eligibility criteria in MF. There is increasing evidence of heterogeneity in molecular disease grade, beyond the clinical manifestations which have traditionally guided transplant timing. Exploring the physiological consequences of disease chronicity unique to MF, acknowledging the heterogeneity in disease grade, and using advanced prognostic models, molecular diagnostics and other organ function diagnostic tools, we present an innovative review of strategies with the potential to improve transplant outcomes in this disease. Larger, prospective studies which consider the impact of molecular‐based disease grade are needed for MF transplantation. Abstract :